Perancangan Media Informasi Mengenai Hewan Reptil Chameleon Dalam Buku Ensiklopedia - Syakur, Savira Alvina; Hidayatullah, Taufan (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2021)
The design of one of the reptile animals starting from its shape and ability, the reptile animal is Chameleon. Many of these animals do not understand the shape as well as its characteristics. As for what makes the background of this design because this Chameleon animal has its own charm, starting from its ability to change its color and also as a tame pet and also has a value in the social environment, this Chameleon animal is an imported animal. Chameleon is an animal that has its own love, but many also think that Chameleon is an animal that is not right to be kept. Therefore, it is important for an information medium in which there is a description of Chameleon animals which are amazing animals and how to keep Chameleon using simple and easy to understand language so that keeping Chameleon in the community is no longer a difficult activity to do. The design solution that will be made is to present an information media about Chameleon reptiles, which is an encyclopedia book that clearly explains the types of Chameleon to how to care for Chameleon.